Working with Indigenous and local knowledge (ILK) in large‐scale ecological assessments: Reviewing the experience of the IPBES Global Assessment. Issue 9 (28th July 2020) - McElwee, Pamela; Fernández‐Llamazares, Álvaro; Aumeeruddy‐Thomas, Yildiz; Babai, Dániel; Bates, Peter; Galvin, Kathleen; Guèze, Maximilien; Liu, Jianguo; Molnár, Zsolt; Ngo, Hien T.; Reyes‐García, Victoria; Roy Chowdhury, Rinku; et al.
Abstract: There have been calls for greater inclusion of Indigenous and local knowledge (ILK) in applied ecosystems research and ecological assessments. The Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services (IPBES) Global Assessment (GA) is the first global scale assessment to systematically engage with ILK and issues of concern to Indigenous peoples and local communities (IPLC). In this paper, we review and reflect on how the GA worked with ILK and lessons learned. The GA engaged in critical evaluation and synthesis of existing evidence from multiple sources, using several deliberative steps: having specific authors and questions focus on ILK; integrating inputs from ILK across all chapters; organizing dialogue workshops; issuing calls for contributions to identify other forms and systems of knowledge; and encouraging IPLC to be key stakeholders and contributors. We identify content areas where attention to ILK was particularly important for questions in applied ecology. These include: (a) enriching understandings of nature and its contributions to people, including ecosystem services; (b) assisting in assessing and monitoring ecosystem change; (c) contributing to international targets and scenario development to achieve global goals like the Aichi Biodiversity Targets and the Sustainable Development Goals and (d) generating inclusive and policy‐relevant options for people and nature. However, challenges in engaging different knowledge systems were also encountered. Policy implications . The Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services (IPBES) Global Assessment (GA) demonstrated the importance of Indigenous peoples and local communities (IPLC) to global biodiversity conservation and ecosystem management. Initiatives seeking to engage Indigenous and local knowledge (ILK) can learn from the experience of the GA. Successfully bringing ILK into assessment processes and policy arenas requires a deliberate framework and approach from the start that facilitates recognition of different knowledge systems, identifies questions relevant at various scales, mobilizes funding and recognizes time required and engages networks of stakeholders with diverse worldviews. In turn, fostering inclusion of ILK and partnering with IPLC can help future assessments understand how natural and cultural systems co‐produce each other, identify trends of change through diverse biocultural indicators and improve sustainable development goals and policies. Abstract : The Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services (IPBES) Global Assessment (GA) demonstrated the importance of Indigenous peoples and local communities (IPLC) to global biodiversity conservation and ecosystem management. Initiatives seeking to engage Indigenous and local knowledge (ILK) can learn from the experience of the GA. Successfully bringing ILK into assessment processes and policy arenas requires a deliberate framework and approach from the start that facilitates recognition of different knowledge systems, identifies questions relevant at various scales, mobilizes funding and recognizes time required and engages networks of stakeholders with diverse worldviews. In turn, fostering inclusion of ILK and partnering with IPLC can help future assessments understand how natural and cultural systems co‐produce each other, identify trends of change through diverse biocultural indicators and improve sustainable development goals and policies. Resumen: Se ha reclamado una mayor inclusión del conocimiento Indígena y local en la investigación en ecología aplicada así como en evaluaciones ecológicas. La Evaluación Global de la Plataforma Intergubernamental Científico‐Normativa sobre Diversidad Biológica y Servicios de los Ecosistemas (IPBES, por sus siglas en inglés) es la primera evaluación a nivel global en trabajar sistemáticamente con conocimiento Indígena y local y con asuntos que conciernen a Pueblos Indígenas y comunidades locales. En este artículo, revisamos y reflexionamos sobre cómo se enfocó el trabajo con conocimiento Indígena y local en la Evaluación Global, y la experiencia adquirida en este proceso. La Evaluación Global examinó de forma crítica y sintetizó la evidencia de múltiples fuentes, siguiendo varios pasos deliberativos: incorporando autores específicos y preguntas focalizadas en conocimiento Indígena y local; integrando aportaciones del conocimiento Indígena y local a través de todos sus capítulos; organizando talleres de diálogo; abriendo convocatorias para recibir contribuciones e identificar otras formas y sistemas de conocimiento; y alentando la participación y contribución de Pueblos Indígenas y comunidades locales como partes interesadas. Identificamos varios temas en los que la atención al conocimiento Indígena y local es particularmente importante en relación a cuestiones de ecología aplicada. Éstos incluyen: (a) profundizar en la comprensión de la naturaleza y sus contribuciones a las personas, incluyendo los servicios de los ecosistemas; (b) asistir en la evaluación y el monitoreo de cambios en los ecosistemas; (c) contribuir a metas internacionales y al desarrollo de escenarios para cumplir con objetivos globales como las Metas de Aichi para la Diversidad Biológica y los Objetivos de Desarrollo Sostenible; y (d) generar opciones inclusivas y de relevancia política para la naturaleza y las personas. No obstante, también hubo desafíos a la hora de conectar diferentes sistemas de conocimiento de forma transparente, equitativa y legítima. Implicaciones políticas . La Evaluación Global demostró la importancia mundial de los Pueblos Indígenas y las comunidades locales para la conservación de la biodiversidad y el manejo de los ecosistemas. Iniciativas que aspiren a incluir el conocimiento Indígena y local pueden inspirarse en la experiencia de la Evaluación Global. Incluir de forma efectiva el conocimiento Indígena y local en procesos de evaluación y en el ámbito político requiere un marco deliberativo y una aproximación de base que faciliten el reconocimiento de diferentes sistemas de conocimiento, identifiquen cuestiones relevantes a varias escalas, movilicen financiación y reconozcan el tiempo necesario, y vinculen a redes de grupos de interés con diversas visiones del mundo. Así mismo, fomentar la inclusión del conocimiento Indígena y local y colaborar con Pueblos Indígenas y comunidades locales puede ayudar a que futuras evaluaciones entiendan mejor las interdependencias entre sistemas culturales y naturales, identifiquen tendencias de cambio a través de indicadores bioculturales, y contribuyan a mejorar objetivos y políticas de desarrollo sostenible.